Room temperature structural, and ferromagnetic behaviour of Mn, Fe and Mn/ Fe codoped In2O3 Nanocrystalline - Sanjay Kumar; Virendra Kumar; Manoj Kumar Bansal; Arvind Mishra; Vimlesh Mishra (Results in Optics)
Manganese & iron-doped indium oxide dilute magnetic semiconductor (DMS) powder was synthesized by solid-state reaction method. The effect of Mn & Fe doping on magnetic, optical, and structural properties of (In)0.985(Mn).015O and (In)0.985(Fe).015O have been systematically studied. The polycrystalline cubic structure has been confirmed by an X-ray diffraction pattern. It is also being reported that the optical band gap increases from 3.8 eV to 4.2 eV for Mn-doped while 3.8 eV to 4.4 eV for Fe-doped samples. FTIR spectra reveal the occupancy of In-O and In-O-H absorption bands. EDAX confirms the occupancy of Fe, O, In, and Mn elements in the prepared samples. M−H plot indicates superparamagnetic behavior in Mn-doped In2O3.